GEOPOLITICS AND INNOVATION IN THE BRAZILIAN POTASSI: REMINERALIZERS, SOVEREIGNTY AND SUSTAINABILITY IN BRAZILIAN AGRIBUSINESS - Moacir Costa Macêdo, Manoel; de Araújo Mendonça Sobrinho, José; Edstron Secundino Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research investigates the Geopolitics and Innovation in the Brazilian Potassium Cycle, analyzing the transition from external dependence to mineral sovereignty through soil remineralizers. The significance of the theme lies in the strategic vulnerability of agribusiness, which imports approximately 95% of its potassium chloride, exposing food security to geopolitical and logistical risks in Eastern Europe. The methodology is based on a comprehensive literature review and the analysis of national and international case studies, integrating knowledge from mineralogy, agronomy, and international law under the aegis of the WTO. The findings indicate that the utilization of national geological masses—such as phonolites and “verdete”—associated with biotechnological bioactivation, constitutes a strategic survival imperative. This study demonstrates that Brazil possesses the geological potential to reduce external dependence, transforming regional agrominerals into instruments of sustainability and economic resilience. The convergence between integrated policies, such as the National Fertilizer Plan, and industrial innovation serves as the definitive passport to Brazilian agro-environmental leadership in the 21st century.